The Strategic Role of Classroom Management in Improving Student Learning Achievement - Fitriana, Allysha Syatifa (SABA JAYA PUBLISHER, 2025)
Issues in classroom management often arise due to a lack of student discipline, challenges in teacher authority, and external factors such as social problems faced by students. These can disrupt the smooth flow of the learning process and reduce its effectiveness. This study aims to analyze effective classroom management strategies and identify obstacles that may affect the success of learning. The method used in this study is a literature review, which examines various references related to classroom management, including theories, strategies, and challenges faced by teachers in practice. The findings show that effective classroom management requires the implementation of varied strategies, such as developing lesson plans that align with the curriculum, applying good communication both verbal and non-verbal, and gaining a deep understanding of students' character and background. Additionally, teachers need to apply the appropriate approach to address discipline issues, such as providing guidance, arranging seating, and offering praise or sanctions accordingly. In conclusion, the success of classroom management heavily depends on the collaboration between teachers, students, educational institutions, parents, and the community, in creating an environment that supports the success of learning and the holistic development of students.